Construction of a three-dimensional S, N co-doped ZIF-67 derivative assisted by PEDOT nanowires and its application in rechargeable Zn–air batteries. (26th November 2021) - Xiang, Wenjuan; Li, Jing; Ma, Jinfu; Sheng, Zhilin; Lu, Hui; Yang, Shaolin
Abstract : PEDOT nanowires were obtained before pyrolysis to inhibit structural collapse and anisotropic shrinkage of the ZIF-67 in the pyrolysis process, and S, N co-doping is realized at the same time. The synthesized Co/C@NS NWs exhibit excellent performance towards ORR and OER. Abstract : A Co–zeolite imidazole ester framework (ZIF-67) has excellent electrochemical performance for the oxygen reduction reaction (ORR), but the structural stability is still the key problem to be solved. PEDOT is a polymer of EDOT (3, 4-ethylenedioxythiophene monomer), a π-conjugated conductive polymer with superior performance and wide application. It has a rigid and linear conformation, which is necessary to maintain the integrity of the material structure and prevent collapse. And this conformation is also conducive to charge transport and crystallization, resulting in good performance of high charge/discharge capacities, fast response time and high sensing ability. Herein through the pre-implantation of PEDOT nanowires, the structural collapse, anisotropic shrinkage and Co atom agglomeration of ZIF-67 in the pyrolysis process were inhibited, and S, N co-doping was realized at the same time. The XRD, SEM, TEM and XPS characterization studies prove that PEDOT nanowires successfully embedded in the ZIF-67 structure, and N and S are doped into the carbon framework of the catalyst. The synthesized catalyst has a regular hexahedral morphology, interconnected three-dimensional (3D) nanowire (NW) framework and graphitized carbon coated Co nanoparticles (Co/C@NS NWs), endowing it with excellent bifunctional catalytic performance toward oxygen. The initial potential was 0.91 V ( vs. RHE) and the limiting current density was −4.8 mA cm −2 for the ORR. The potential required to reach 10 mA cm −2 is only 1.55 V ( vs. RHE) and the Tafel slope for the oxygen evolution reaction (OER) is relatively low (100 mV dec −1 ). An open circuit voltage of 1.46 V for Zn–air battery cathodes catalyzed by Co/C@NS NWs at a discharge power density of 129.3 mWcm −2 is obtained, and the specific capacity at a discharge current density of 10 mA cm −1 is 800 mA h gZn −1 . The voltages show no obvious change for a 35 h continuous discharge/charge cycle experiment. Therefore, this work provides a new inspiration for the design and development of high-performance non-noble metal carbon-based bifunctional oxygen electrocatalysts.